2022
DOI: 10.1177/02611929221143774
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Transcription Regulators Differentiate Human Umbilical Cord Mesenchymal Stem Cells into Cardiac Cells

Abstract: Stem cell-based therapy presents an attractive alternative to conventional therapies for degenerative diseases. Numerous studies have investigated the capability of human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) to contribute to the regeneration of cardiomyocytes, and the results have encouraged further basic and clinical studies on the MSC-based treatment of cardiomyopathies. This study aimed to determine the potential of cardiomyogenic transcription factors in differentiating hUC-MSCs into ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Study investigated that MSCs are capable to differentiate into osteogenic, chondrogenic, and adipogenic lineages. However, current techniques for inducing differentiation have been improved, and MSCs derived from different tissue sources can be differentiated into any type of body cell[ 64 ]. It has been found that after 21 d of induction with osteogenic, chondrogenic, and adipogenic induction media, the MSCs differentiated, as confirmed by the presence of calcium deposits, proteoglycan formation, and oil droplets, respectively[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study investigated that MSCs are capable to differentiate into osteogenic, chondrogenic, and adipogenic lineages. However, current techniques for inducing differentiation have been improved, and MSCs derived from different tissue sources can be differentiated into any type of body cell[ 64 ]. It has been found that after 21 d of induction with osteogenic, chondrogenic, and adipogenic induction media, the MSCs differentiated, as confirmed by the presence of calcium deposits, proteoglycan formation, and oil droplets, respectively[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent, rapid expansion of stem cell-based research, and its successful translation into therapy, presents an opportunity for significant advancements in developing novel treatments in the future. Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) that may contribute to the regeneration of cardiomyocytes, were the subject of the study by Shafique et al 3 By overexpressing GATA-4 and Nkx-2.5 in hUC-MSCs, following lentiviral gene transduction, the authors demonstrated the potential of these factors to act synergistically in the activation of downstream cardiac transcription factors, facilitating the differentiation of hUC-MSCs into cardiac-like cells in vitro . Such findings may be useful for developing in vivo treatments following myocardial infarction.…”
mentioning
confidence: 99%